Effects of Task Switching In Baggage Screeners. (December 2020) - Zish, Kevin; Erchov, Simone; Eisert, Jesse; McKee, Charles; Endres, Daniel; Band, David
Using a visual search and decision-making task, we investigated common task switching effects on baggage screeners. Like the general population, baggage screeners perform best when there is no task switching as shown by a high sustained d' and fast decision time. Although baggage screeners continue to improve throughout the task, task switching results in functional decay of the memory for the current decision-criterion.